Beyond Allyship: Motivations for Advantaged Group Members to Engage in Action for Disadvantaged Groups - Radke, Helena R. M.; Kutlaca, Maja; Siem, Birte; Wright, Stephen C.; Becker, Julia C. (Personality and social psychology review, 2020)
White Americans who participate in the Black Lives Matter movement, men who attended the Women’s March, and people from the Global North who work to reduce poverty in the Global South—advantaged group members (sometimes referred to as allies) often engage in action for disadvantaged groups. Tensions can arise, however, over the inclusion of advantaged group members in these movements, which we argue can partly be explained by their motivations to participate. We propose that advantaged group members can be motivated to participate in these movements (a) to improve the status of the disadvantaged group, (b) on the condition that the status of their own group is maintained, (c) to meet their own personal needs, and (d) because this behavior aligns with their moral beliefs. We identify potential antecedents and behavioral outcomes associated with these motivations before describing the theoretical contribution our article makes to the psychological literature.